2021
DOI: 10.1177/1556984521994206
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem Does Not Prevent Postoperative Atrial Fibrillation After Thoracoscopic Lobectomy

Abstract: Objective Thoracoscopic lobectomy is associated with lower rates of adverse events compared to thoracotomy. Despite this, postoperative atrial fibrillation (POAF) occurs in at least 10% of patients. Our objective is to determine if prophylaxis with diltiazem significantly reduced POAF events. Methods Patients without prior history of atrial fibrillation who underwent thoracoscopic lobectomy from 2007 to 2016 at one institution were analyzed in a retrospective cohort study utilizing a prospective database. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…At the same time, its use was associated with several side effects [67]. Lederer et al, in a very recent study, showed that diltiazem prophylaxis was not useful in reducing POAF incidence after thoracoscopic lobectomy [68].…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…At the same time, its use was associated with several side effects [67]. Lederer et al, in a very recent study, showed that diltiazem prophylaxis was not useful in reducing POAF incidence after thoracoscopic lobectomy [68].…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…In a study conducted by Van Mieghem et al, verapamil demonstrated superiority over placebo in decreasing the incidence of POAF after pulmonary surgery; however, it also induced bradycardia and hypotension in a significant number of patients ( 88 ). Nevertheless, there exist several studies with conflicting outcomes; for instance, diltiazem prophylaxis did not exhibit efficacy in reducing the occurrence of POAF after thoracoscopic lobectomy ( 89 , 90 ). Furthermore, a recent investigation by Hochreiter et al revealed that diltiazem prophylaxis failed to reduce the incidence of POAF after thoracoabdominal esophagectomy and instead led to increased occurrences of bradycardia and norepinephrine requirements ( 91 ).…”
Section: Introductionmentioning
confidence: 99%